Comparative study of two rolling bond process for super-thick Q235B - Guanghui Zhao; Qingxue Huang; Cunlong Zhou; Zhanjie Zhang; Lifeng Ma; Xiaogang Wang (Functional Materials, 2016)
In paper, two rolling bond processes for heavy-gauge steel plate Q235B were studied and the processes were simulated by MARC software. The mechanical properties and microstructure at the interface were comparative analyzed for the two bonded plates using different rolling process. Using MARC software analysis for two rolling process, the ratio of equivalent stress in rolling process /yield stress in current temperature from surface to center portion was relatively uniform for rolling bonded.